Estimation of the age at natural menopause in a population-based study of Polish women - Kaczmarek, Maria (Menopause Review/Przegląd Menopauzalny, 2007)
This paper provides an estimation of the age at natural menopause in a population-based sample of Polish women. 7183 women from all social strata of the non-clinical population, and aged between 35 and 65 years were investigated in a cross-sectional survey of middle aged women’s health (WOMID). The survey was carried out across Poland in 2000-2004. The demographic, social, lifestyle behaviour and reproductive history aspects of the menopause-specific questionnaire were examined. Non-parametric Kaplan-Meier cumulative survivorship estimates were used to assess the median age at natural menopause. The overall median age at natural menopause was 51.25 years; 25th percentile 49; 75th percentile 54 years. Variation in age at menopause revealed the age range from 45 years to 56 years. Temporal changes in the age at menopause were not demonstrated in the sample (p>0.05 for differences between two age cohorts). Worldwide comparative data of the age at natural menopause showed its interpopulation age variation. The median age at menopause in Polish women was similar to women from Europe, Australia and the U.S.A. Natural menopause in Poles occurred much later than in women from Africa and Asia (apart from Japan). The present estimate of the age at natural menopause in Poland may be used as a measure of health for the growing number of Polish women whose survival is predicted at almost 30 years after menopause.